Analisa Pengaruh Hedonic dan Utilitarian Value Terhadap Repurchase Intention pada Industri Pusat Kebugaran Kelas Menengah Atas di Sidoarjo - Samsi Dimastita Bagyarta (Jurnal Strategi Pemasaran, 2014)
An increasing rate of Indonesian economic growth has pushed the middle class people to the greater number. This condition also makes the middle class consumers to become more consumptive, especially on the need for leisure. This consumptive behavior can be traced by exhibiting the growth of the middle class fitness center, which is significantly faster than the exclusive one. There are two attributes to define how the consumptive behavior works in the middle class fitness center, it is by using hedonic value and utilitarian value as the primary consideration of buying process. The researcher hypothesized that those two different attributes have direct relationships to customer satisfaction and repurchase intention, as this paper would reveal the truth of those ideas. This research uses Partial Least Square (PLS) to analyze the relationships between the variables. Also, there are 120 respondents involved to gather the data.